"From Boots on 'til Boots Off": Collecting Greenland with Explorer Louise Arner Boyd (1887-1972). Issue 4 (December 2018) - Kafarowski, Joanna
A notable 20th-century female explorer, California-born Louise Arner Boyd (1887-1972) was also a world expert on Greenland. As it was in Boyd's time, Greenland remains a remote and little-known area of the world. She was showered with honors and respected by her polar colleagues. As a result of organizing and participating in seven hazardous Arctic expeditions between 1926 and 1955, she amassed a significant collection of maps, photographs, films, and books about this area. The majority of photographs and films were taken by Boyd, while many of the maps were based on information gathered during her Arctic adventures. Meticulous and detail oriented, Louise Arner Boyd was driven by her passion for the north. Boyd traveled to Greenland, photographing geographic landforms and gathering scientific information. Her expertise on Greenland was recognized by the American government during World War II and her collection put at the government's disposal. Contemporary Norwegian glaciologists still use her existing 1930s photographs to track environmental change. Today, the many accomplishments of Louise Arner Boyd have been forgotten, and her magnificent collection, which was an invaluable asset to the Allied effort during World War II, has been dispersed.